In vitro and preclinical evaluation of the antifungal activity of 6-methoxy-1 H-indole-2-carboxylic acid produced by Bacillus toyonensis strain OQ071612 formulated as nanosponge hydrogel - Sayed E. El-Sayed; Neveen A. Abdelaziz; Ghadir S. El-Housseiny; Khaled M. Aboshanab (Microbial Cell Factories)
Abstract Background In a previous study, 6-methoxy-1 H-indole-2-carboxylic acid (MICA) was isolated from the culture broth of Bacillus toyonensis strain OQ071612 soil isolate in our laboratory, and it demonstrated promising antifungal activities. The current study was designed to create a nanosponge (NS)-hydrogel (HG)-containing MICA followed by in vitro and preclinical evaluation for potential clinical use in the topical treatment of mycotic infections. Results The enhanced NS formula was created using the Box Behnken Design (BBD), with independent process parameters including polyvinyl alcohol percentage (w/v%), homogenization time, speed and polymer: linker ratio. Dependent parameters were particle size (PS), polydispersity index (PDI), and entrapment efficiency percent (EE%). A hydrogel was formulated from the NS. In vitro drug release data indicated that the hydrogel best matched Higuchi’s kinetic release model. The formulated NS-HG was stable and when compared to fluconazole, it exhibited increased antimycotic activity against C. albicans. An in vivo investigation revealed that MICA-NS-HG enhanced survival rates, wound gap repair, wound reduction, and inflammation inhibition. Masson’s trichrome staining and histological analyses revealed increased collagen deposition and improved healing. Moreover, MICA hydrogel exhibited 1.5-fold greater permeability through rat skin compared to the control, 1% isoconazole. Conclusion The NS-HG formulation is a viable vehicle for better and more effective topical release of MICA. These findings represent a significant advancement in the formulation of MICA derived from naturally occurring soil bacteria.